Mandibular propulsion and dental implant rehabilitation for an edentulous patient with class II malocclusion and severe obstructive sleep apnea - Lenganey Hugues; Rasteau Simon; Minassian Harmik; Murcier Gregory; Jouan Robin; Borgnat Florent (EDP Sciences, 2021)
Introduction: Orthognathic surgery can be a treatment for occlusal, oro-facial functional disorders and esthetics discrepancies as well as for obstructive sleep apnea. It is often practiced after an orthodontic preparation, but in edentulous patients, the preparation can be replaced with implant supported prosthesis to simulate the final occlusion. Observation: A patient presenting severe obstructive sleep apnea, vertical and sagittal insufficiency of the lower third of the face and poor dental health was treated with a guided mandibular advancement and an almost complete implant supported prosthesis rehabilitation. At first, the implants were placed and immediately loaded, giving the patient a class 2 occlusion. Then, an orthognathic surgery was performed, giving the patient a class 1 occlusion, and then the final prosthesis was made. Commentaries: The interest of this case is the combined treatment of the obstructive sleep apnea, the dental and facial deformities by mandibular retrognathia and the edentulous jaws. The gold standard for obstructive sleep apnea is a maxillary and mandibular advancement. In this case, for esthetic and anatomic reasons, a mandible propulsion alone has been performed, showing a positive and stable result for the treatment of obstructive sleep apnea. The use of surgical guide permitted to plan the treatment with more accuracy. Conclusion: This case combines a fixed prosthetic rehabilitation, which permitted to guide the orthognathic surgery and the treatment of obstructive sleep apnea.